Community health diagnosis of Bokhim village development committee (VDC), Bhojpur, Nepal. - Pradhan, Prajwal Mani Ghimire, Raju Ghimire, Pradip Baskota, Sweta Sharma, Nirmala Sharma, Sweekriti Regmi, Sophika Rawal, Shweta Lohani, Shilpa Kharel, Preeti
SUMMARY: Bokhim borders Bhojpur VDC & Bhaisipankha VDC at East & South, Dawa at west. Bokhim hosts a majority of Janajati people. Panoramic Hill top Suntale from where one can view Sankhuwasabha district in east & Sapta koshi in north is one of the pride of the VDC. Friendly & naïve rural people are the major assets of Bokhim. Besides, many ongoing development projects are in pipeline to execution here. Bokhim has no electricity & no automobiles. The General objective of our study was: To assess the health status of the population, their health needs & plan, implement a Micro-Health Project to improve the health status of Bokhim VDC, Bhojpur District. The study was descriptive in nature. The field study duration was of one month (23 Shrawan- 21 Bhadra). A total of 230 Questionnaires were filled (i.e. 35.22% of the total household (653) of Bokhim). Total household of a ward were enlisted by community people themselves during the process of social mapping, which was later compared with the household list from govt. list; after the completion of list random sampling technique was adopted. The unit of sampling was individual household. Systematic random sampling technique was adopted. Questionnaire, FGD on specific issues, PLA tools like social mapping, pair wise ranking, mobility map were our data collection tools & techniques used was to be as participatory as possible. Verbal informed consent of interviewee was taken before filling the questionnaire; participant's names of FGD are not disclosed for maintaining confidentiality. Our study was based on sample which was presumed to be representative at a level of 35.22 %. We urge to take this report as an indicative rather than definitive in aspect of reflecting demographic & other health characteristics of Bokhim VDC. Our sample de-jure enumerated the total Population of 230 household was to be 1334 (640 were male & 694 female). Out of 230 household, by caste; majorities of households were Janajati 66.95% (154), 16.08 % (37) Brahmin household, 11.73 % (27) were Chhetri, 5.21 % (12) were Dalit. Out of 230 household, by religion; majority was of Hindu 141 (61.30%), 51 (22.17%) of Buddhist, 36 (15.65%) of Kirat & 2 (0.8695%) of Christian. The Crude Birth Rate was calculated to be total birth 4.34 per 1000 live birth. The Crude Death Rate was calculated to be total Death 10.494 per 1000 deaths. The major source of income was from Agriculture (83%), others 17% (Teaching, labor, craftsmanship, foreign employment). Thirty one percent of household that at least one person had traveled away from the household at some time in past 12 months which is grossly comparable with 37 % of NDHS, 2006i. Astounding majority of household is headed by men 98.1%. Average size of Household was 5.8 which is in sparingly equal to rural household size estimates of 5.0 (rural areas) NDHS, 20061. Literacy rate was among female was found to be 40.63% of total female population, whereas, 52.34 % of total male population were literate. An average of 46.25 % of the total population of Bokhim VDC was literate. A majority 76.08 % responded that they knew about ORS for management of Diarrhea & only 72.17 % prompted for its use in diarrhea. Surprisingly, 57.4 % still prepared ORS using techniques which were completely unacceptable & posed serious health risks On being asked upon the reason for not to go for ANC visit, 16.95% of people thought ANC visit was necessary & 9.1% stated they didn't knew about ANC Visits & 7.82% didn't want to answer the reason for not visiting for ANC. 78.26 % of household were satisfied with the services that they were getting from their local health institution. 91.73 % of household answered that now they need to spend only 10 minutes average to fill & return with drinking water. Overall 24.78 % of the household used some type of purification technique. 87.82 % of the household had toilet in their homes & 12.18 % of the household had no toilet in their homes. First community presentation on 25th August 2008 at Panchakanya mavi at ward 1. Needs were discussed & prioritized using pair wise ranking method. Safe motherhood got 51 & left other two needs far behind. General objective of our MHP was: To increase knowledge regarding safe motherhood in women of reproductive age group at Bokhim VDC. The critical contents were also finalized in close discussion with FCHVs which were: Nutrition during pregnancy, Importance of ANC & PNC Visit, Complications during Pregnancy & Post-partum, Safe Abortion. MHP implemented on 27 August at ward 3 at Shree Jagadisawori primary school. The Pre & Post test method was considered suitable for the purpose of evaluating the effectiveness of health messages because they yielded the actual difference from where they were to where they are whereas specific questions were asked related to program structure, content & effectiveness of presenters. The final community presentation was scheduled on 31 August 2008. The final district level presentation was scheduled to be of District level on 5 September 2008. Leading health problems of the VDC were: infectious diseases, safe motherhood & child health problems. Based on these findings, the subjective projection of Bokhim in future happens to be not satisfactory; it has to focus on its level of education, status of mother & children. With impetus on these three specific area we are happy to say that Bokhim is certain to achieve MDGs in due time of 2015. Evaluation of MHP has shown promising results; however for the sustainability of these achievements frequent community level programs have to be run. It also curtails the fact that proper information in appropriate way certainly improves the level of awareness regarding health & its Issues.